DAMPAK FAKTOR FUNDAMENTAL MAKROEKONOMI TERHADAP KURS PADA SISTEM NILAI TUKAR MENGAMBANG BEBAS DI TIGA NEGARA ASEAN - Abdulloh Azzam; Indra Suhendra; Sugeng Setyadi (Jurnal Ekonomi-Qu, 2018)
The aim of this research is to analyze the influence of macroeconomic fundamental variables such as balance of trade, trade liberalization, difference of interest rate, interest rate, economic growth and government debt to floating exchange rate in the ASEAN countries in the period of 1990-2005. This research use time series data collected from World Bank publication. Panel data analysis is used to analysis the regression model. The research result shows that simultaneously some variables such as balance of trade, trade liberalization, difference of interest rate, interest rate, economic growth and government debt have significant effect to exchange rate variable inASEAN countries in the case of floating exchange rate system. On the other hand, partially, variable of balance of trade, trade liberalization and difference of interest rate have not significant influence to exchange rate variable in ASEAN in the case of floating exchange rate system, while,the variable of interest rate, economic growth, and government debt show have significant effect to exchange rate variable in ASEAN countries in the case of floating exchange rate system.